POLA AKTIVITAS PADA RUANG TERBUKA TAMAN BAMBU CIPAYUNG JAKARTA TIMUR - Rahayu, Azahrani Fira; Kasman (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2020)
Cipayung Bamboo Park is an open space in the East Jakarta area which can be aforum for interaction and recreation for the community. As an open space in EastJakarta, Cipayung Bamboo Park is visited by many people, so that variousactivities appear in it. This study uses a qualitative descriptive method, with theaim of identifying patterns of activity in the use of Cipayung Bamboo Park publicspace. These activity patterns are influenced by the existing system settings. Theobservation method with the type of placed-centered mapping is used todetermine activity patterns in Cipayung Bamboo Park. Observations were made inthe afternoon and evening on weekdays and holidays. The results of this studyindicate that the environmental management of Cipayung Bamboo Parkinfluences activity patterns in spatial use and must accommodate the activities ofits visitors.